The Effect Of Differentiated Instruction On The 9Th Grade Efl Students’ Reading Comprehension Achievement In Jordan - Magableh, Ibrahim Suleiman (2022)
This study follows Explanatory Sequential Design where the quasiexperimental mixed-methods QUAN-qual model is followed. The purpose of the study was to investigate the effectiveness of differentiated instruction on the 9th grade EFL students’ English reading comprehension achievement in Jordan and identify the key benefits of differentiated instruction implementations as well as to find out the key obstacles of its implementation. This study followed the mixed-method design that uses the quantitative and the qualitative data for data collection. A total of 109 male and female grade 9 students, randomly selected using the simple random sampling technique from four different schools, participated in the study. The respondents were divided into two groups. The experimental group of 55 respondents,